COHABITATION THE TRICOLOUR LANGUR AND MULLER’S GIBBON IN PULAU MAJANG RESORT, DANAU SENTARUM NATIONAL PARK - Santoso, Nyoto; Perdhana, Reza Dwiputra; Sutopo (Media Konservasi, 2023)
The interaction between Presbytis chrysomelas ssp. cruciger and Hylobates muelleri which occurs due to the utilization of the same resources has caused the two primates to cohabitate in the Majang Island Resort Area. Information regarding resource use by cohabiting species is very important for their conservation management. The aims of this research are to identify common niches between P. chrysomelas and Muller’s gibbon, to analyze the niche overlap and niche breadth; to find out the forms of spatial cohabitation and the factors that cause cohabitation. Data collection was carried out from July to December 2021. Cohabitation was identified in the use of vertical and horizontal space which is closely related to the availability of feed for both primates. There is overlapping home ranges between the P. chrysomelas and Muller’s gibbon at the study site covering an area of 9.93 ha, and only B stratum (trees with a height of 18 – 30 m) which are used jointly for activity by both primates. The Jaccard index for the association of vertical space use for P. chrysomelas and Muller’s gibbon is 0.33 while the Jaccard index for the number of forage plant species is 0.50. P. chrysomelas ecological niche overlaps 116% with Muller’s gibbon and the H.muelleri ecological niche overlaps 65% with P. chrysomelas’s. Calculation of the ecological niche area of P. chrysomelas is FT = 0.65335, the lower limit and upper limit value is 0.27033 ≤ FT ≥ 0.91288. Meanwhile, for the Muller’s gibbon, the value is FT = 0.46454, the lower and upper limits are 0.04483 ≤ FT ≥ 0.79644. Key words: Cohabitation, Danau Sentarum, Tricolour langur, Muller’s gibbon